1990
DOI: 10.1021/jf00092a043
|View full text |Cite
|
Sign up to set email alerts
|

Pyrethroid metabolism: microsomal oxidase metabolites of (S)-bioallethrin and the six natural pyrethrins

Abstract: Metabolism of the chrysanthemates (S)-bioallethrin, cinerin I, jasmolin I, and pyrethrin I by NADPHdependent oxidases of mouse liver microsomes yields 13-18 metabolites in each case oxidized a t the methyl, methylene, and alkenyl substituents to form alcohols, aldehydes, carboxylic acids, epoxides, and dihydrodiols. Rat microsomes are more specific than mouse microsomes in hydroxylating the @)-methyl substituent of the 2-methylpropenyl moiety compared with other molecular sites. Metabolites in the urine of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…36912-77-3). The last two metabolites were found by Class et al (1990) in urine to partly exist as conjugates. Metabolites were tentatively identified by chemical ionization mass spectrometry, following treatment with diazomethane or diazoethane and trimethylsilylacetamide and high-resolution GC.…”
Section: In Vivo Metabolism Of 1pyrethroid Insecticidesmentioning
confidence: 99%
“…36912-77-3). The last two metabolites were found by Class et al (1990) in urine to partly exist as conjugates. Metabolites were tentatively identified by chemical ionization mass spectrometry, following treatment with diazomethane or diazoethane and trimethylsilylacetamide and high-resolution GC.…”
Section: In Vivo Metabolism Of 1pyrethroid Insecticidesmentioning
confidence: 99%
“…Immunoassay methods are on the one hand comparable cheap and easy to perform, but on the other hand they do not achieve the sensitivity and specificity of analytical methods. For the determination of the internal pyrethrum, allethrin, resmethrin, phenothrin and tetramethrin burden, trans-chrysanthemumdicarboxylic acid (CDCA) turned out to be the relevant biomarker in the urine [10,23]. Regarding the detection of trans-CDCA in human urine there are only two publications available [10,17].…”
Section: Introductionmentioning
confidence: 99%
“…In Rhesus monkeys, however, administration of pyrethrins into the body (100% bioavailability) by avoiding the digestive canal (parenteral studies) showed that 22.5% of the chemical was excreted in the urine seven days after administration (Wester et al, 1992). The compound has been found to rapidly degrade in the stomach by hydrolysis of the ester bond to harmless metabolites (Class et al, 1990). The metabolic fate of pyrethrins in rats has been partially defined in microsomal oxidase system (Casida et al, 1971;Elliott et al, 1972).…”
Section: Birds and Mammalsmentioning
confidence: 99%
“…The metabolic fate of pyrethrins in rats has been partially defined in microsomal oxidase system (Casida et al, 1971;Elliott et al, 1972). The sites of metabolic attack on the pyrethrins and the metabolites (Figure 1 and 2) were determined by Class et al (1990).…”
Section: Birds and Mammalsmentioning
confidence: 99%